Synthesis of novel heterocyclic compounds bearing tetralin moiety of potential anticancer activity targeting the intrinsic apoptotic pathway. Issue 4 (16th February 2023) - Hamdy, Nehal A.; El Sayed, Mardia T.; Hussein, Hoda A. R.; Mounier, Marwa M.; Anwar, Manal M.
Abstract: This study deals with the readily reaction of the enaminone derivative 3 with different reagents to give the corresponding pyrazolo[3, 4- b ]pyridine, pyrazolo[1, 5- a ]pyrimidine, pyrazole, pyrazolopyridazine, dienamide, and pyranone derivatives. In-vitro cytotoxic screening was performed for all analogs against several human cancer cell lines. Compound 21 showed significant anti-breast cancer activity and a safety profile against the normal human cell lines (BJ-1). Furthermore, compound 21 was chosen as a representative example to study its potential apoptotic mechanism in the MCF-7 cancer cell line. It enhanced DNA fragmentation alongside its characteristic effect on tubulin polymerization. In addition, compound 21 up-regulated the pro-apoptotic Bax protein, decreased the Bcl-2 anti-apoptotic protein, and increased p53 and Caspase-7 levels confirming its mitochondrial intrinsic apoptotic activation. Graphical Abstract: UF0001